WAJAH BARU KIRI ISLAM: STUDI GERAKAN FRONT NAHDLIYIN UNTUK KEDAULATAN SUMBER DAYA ALAM (FNKSDA) - M. Ubaidillah (UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
Implementation of development and influence on industrialization should be not understood as is. According to Karl Marx and Antonio Gramci, religion is a condition that absolute works for capitalism and nullify the resistance movement. This condition makes the role of social movements becomes important as a process of awareness and social transformation. Current social movements are constantly produced and have dynamics process. One factor of social movements is still existed because of the opposition to the multinational extractive industry contestation in getting natural resources. One of them is movement of social-environment by youth groups appears in the body of Islamic organizations Nahdlatul Ulama (NU). Lack of sovereignty of natural resources in Indonesia encourages a group of NU youth to build organizations of social-environmental movements that are network-based with NU organization. This movement organization was officially established on 9 December 2013. Initially, there is criticism and disappointment among some NU youths towards the structural NU group and government. Because the elite group of NU, who is sitting structurally, considers less sensitive and concerns with the issue of sovereignty of natural resources and social-environmental sustainability of Indonesia people's lives, especially NU residents.Keywords: NU Young People, Environmental Movement, Organization Social. Implementasi pembangunan dan pengaruh atas industrialisasi seharusnya tidak dipahami sebagai apa adanya. Menurut Karl Marx dan Antonio Gramci, agama adalah syarat Mutlaq proses kerja kapitalisme untuk meniadakan gerakan perlawanan. Hal ini membuat peran gerakan sosial menjadi penting sebagai proses penyadaran dan transformasi sosial. Arus gerakan sosial itu terus-menerus diproduksi dan memiliki dinamika sendiri. Salah satu faktor dari gerakan sosial saat ini masih berlangsung karena perlawanan terhadap kontestasi industri ekstraktif multinasional dalam mendapatkan sumber daya alam. Salah satunya adalah gerakan sosial-lingkungan oleh kelompok pemuda muncul dalam tubuh ormas Islam Nahdlatul Ulama (NU). Kurangnya kedaulatan sumber daya alam di Indonesia mendorong sekelompok pemuda NU membangun organisasi gerakan sosial-lingkungan yang yang berbasis jaringan dengan komunitas NU. Organisasi yang resmi berdiri pada 9 desember 2013, Awalnya muncul kritik dan kekecewaan sebagian pemuda NU terhadap kelompok NU struktural dan pemerintah. Karena kelompok elit NU yang duduk struktural dianggap kurang peka dan peduli terhadap isu kedaulatan sumber daya alam dan kelestarian lingkungan-sosial hidup rakyat Indonesia, khususnya warga NU.Kata kunci: Anak Muda NU, Gerakan Lingkungan, Organisasi Sosial.